Domestic and international dimensions of the Catalan problem: (An Analysis of Political Geography) - Bzhar Abdulsattar Abdul Qader; Ubedullah Hatam Yusef (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Catalonia has repeatedly tried to secede from Spain, the last attempt to dream of independence was the referendum on October 1, 2017, which more than 90% of the people Participants voted to secede, which deepened the problem. Because of the importance of this topic, we have divided our research plan into an introduction and three topics. The first topic deals with the natural resources of the Catalan region as follows. The second topic is devoted to human resources in Catalonia. Topic 3: This topic discusses the future of the Catalan problem and the possibilities of resolving it. Finally, the study has reached several conclusions, and we have also presented several recommendations in order to further enrich the study.